PROBLEMATIKA PENERAPAN PRINSIP SUSTAINABLE DEVELOPMENT DALAM PENGELOLAAN LINGKUNGAN HIDUP DAN IMPLIKASINYA TERHADAP PEMENUHAN HAM - suardi, suardi (FIAT JUSTISIA, 2014)
The principle of sustainable development in environmental management is a principle that was born out of responses to the serious environmental damages and give bad effects for human survival, the more damaged of the environment, the higher the threat to humanity itself. Therefore, development is a process of fulfilling human needs that supported on the carrying capacity of the optimal environment. Thus, the higher carrying capacity of environment makes the better stability for human life, conversely the higher human needs in life should be supported by the data support of good environment, so that it can function as a life supporting system. In the implementation, the principle of sustainable development has experienced the complex problems in implementing the balance of human life needs and also the environment, as a result, the environmental damage becomes severe and seemed not able to overcome, people assume that natural resources is the material that should be exploited for fulfilling the human needs. Therefore, environmental management geared to optimize natural resources as a supplier of material needs. By paying attention to that concept, then, environment is seen as a mere object, in turn, the environment can not be saved. Where as the concept of sustainable development requires a balance between human needs and environmental capacity. Hence, the future generations also have the right to enjoy a good and healthy environment as part of their human rights in the future. If the present generation does not pay attention those things, then, the present generation can be said violating the human rights of future generations.Â Keywords: Problematic of Applying the Principle of Sustainable Development, Human Rights.